Physiological Responses of Cucumber Seedlings to Different Supplemental Light Duration of Red and Blue LED - Wang, Shuya; Fang, Hua; Xie, Jianming; Wu, Yue; Tang, Zhongqi; Liu, Zeci; Lv, Jian; Yu, Jihua (Frontiers in Plant Science, 2021)
Normal development of plants is inhibited by inadequate light in winter in greenhouses in Northwest China. Growth lamps, using light-emitting diodes (LED) with red blue light (7R2B) were used to supplement daylight for one, two, and three hours. Seedling growth, photosynthesis and photosynthetic product, the Calvin cycle key and sugar metabolism-related enzymes and their encoding genes and the light signal sensing regulation of key gene expression were studied in greenhouse cucumbers under three treatments to determine the best supplemental light durations to enhance cucumber cultivation in greenhouses in winter. Treatment with LED red and blue light for three hours significantly promoted growth and development of cucumbers, root growth, and dry matter accumulation. It improved the photosynthetic rate, photosynthetic pigment content, and light energy utilization efficiency in cucumbers. Supplementation with red and blue LED light for three hours upregulated the expression levels of key genes encoding the Calvin cycle and enzymes related to sugar metabolism in cucumber leaves, this promoted the synthesis and accumulation of photosynthates. The expression levels of phytochrome B, cryptochrome 1, and hypocotyl 5 in cucumber leaves were also significantly up-regulated after 3 h of light supplementation. Three hours combined LED red and blue light should be used to supplement natural light to enhance cucumber cultivation in greenhouses in winter.